2018
DOI: 10.1200/jop.18.00110
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Chemotherapy Capabilities in Rural Hospitals: Implementation of a Telechemotherapy Model (QReCS) in North Queensland, Australia

Abstract: Implementation of the QReCS model across a large geographic region is feasible with acceptable safety profiles. Leadership by and collaboration among clinicians and managers, adequacy of resources and common governance are key enablers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 16 publications
(17 reference statements)
0
47
0
Order By: Relevance
“…10 Despite these potential issues, groups such as Sabesan et al have reported similar outcomes in patients from regional and remote Australia managed using telehealth and a structured remote chemotherapy service, compared to those managed face-to-face. 11 It important that potential challenges are explored with clinicians at their J o u r n a l P r e -p r o o f healthcare services and that solutions are instigated, such as formal education programs on how to conduct effective telehealth appointments, pathways for alternating face to face/telehealth reviews and utilising the patients' local health care provider to assist with patient examination. 10,11 Additionally, clinicians should remain involved in the process of selecting clinical scenarios where telehealth should and should not be utilised, rather than this being driven by hospital administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Despite these potential issues, groups such as Sabesan et al have reported similar outcomes in patients from regional and remote Australia managed using telehealth and a structured remote chemotherapy service, compared to those managed face-to-face. 11 It important that potential challenges are explored with clinicians at their J o u r n a l P r e -p r o o f healthcare services and that solutions are instigated, such as formal education programs on how to conduct effective telehealth appointments, pathways for alternating face to face/telehealth reviews and utilising the patients' local health care provider to assist with patient examination. 10,11 Additionally, clinicians should remain involved in the process of selecting clinical scenarios where telehealth should and should not be utilised, rather than this being driven by hospital administration.…”
Section: Discussionmentioning
confidence: 99%
“…11 It important that potential challenges are explored with clinicians at their J o u r n a l P r e -p r o o f healthcare services and that solutions are instigated, such as formal education programs on how to conduct effective telehealth appointments, pathways for alternating face to face/telehealth reviews and utilising the patients' local health care provider to assist with patient examination. 10,11 Additionally, clinicians should remain involved in the process of selecting clinical scenarios where telehealth should and should not be utilised, rather than this being driven by hospital administration. The variation in telehealth utilisation and in particular videoconference across regions may also reflect differences in time available for patient consultations in difference regions, impacted differently by COVID-19, differences in widely available technology, cultural differences or differences in billing structure.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, many governments have restricted funding for telehealth to non-primary care doctors, such as referred specialist medical services which are the least accessible medical service in rural areas. 47 However, new government policies during the COVID-19 pandemic in Australia and Canada started to fund rural PHC teams to use telephone and video consultations. This funding is in recognition of the role that telehealth plays in PHC in non-contact healthcare for protecting health workers and the community from infection.…”
Section: Responsementioning
confidence: 99%
“…TH has enabled this during social restrictions and can be used for all mediums of care delivery, such as outpatient, pre‐therapy reviews, pre‐habilitation programmes, preparation for surgery, acute and late effects monitoring, chemotherapy and systemic treatment delivery ('telechemotherapy') and conduct of clinical trials ('teletrials') 5−7 . The COVID‐19 pandemic response has demonstrated that healthcare providers and patients are willing to embrace TH.…”
mentioning
confidence: 99%